Resistance narratives in Laut Bercerita and The Long Walk through the lens of hidden transcript theory - Karkono Karkono; Natanael Ricky Putra; Azizatuz Zahro' (Gelar: Jurnal Seni Budaya, 2025)
This study investigates how hidden transcripts function as covert resistance in Laut Bercerita by Leila S. Chudori and The Long Walk by Stephen King. The research specifically aims to (1) identify and classify symbolic resistance (indirect signs of refusal), discursive resistance (subtle counter-narratives), and gestures of resistance (defiance body signal), and (2) compare how these forms emerge under Indonesia’s New Order and King’s dystopian authoritarian system. Using James C. Scott’s resistance theory, the study applies qualitative close reading, thematic coding of resistance expressions, and cross-textual comparison. Findings show that both novels construct hidden transcripts to critique state domination through layered symbolic and narrative strategies. However, Laut Bercerita foregrounds communal memory and coded mourning rituals, while The Long Walk emphasizes individual bodily endurance as muted protest. These variations indicate that covert resistance is shaped by political repression and cultural frames of suffering. The study contributes to resistance literature by demonstrating how fictional texts extend Scott’s theory and highlighting the value of comparative literature in revealing oppressive structures. The novelty of this study lies in its cross-regime comparative approach, which integrates Scott’s resistance framework with hidden transcript analysis to uncover previously unexamined patterns of covert dissent in two politically and culturally distinct novels.